Arabinoxylan Attenuates Type 2 Diabetes by Improvement of Carbohydrate, Lipid, and Amino Acid Metabolism. Issue 20 (27th September 2018) - Nie, Qixing; Chen, Haihong; Hu, Jielun; Gao, He; Fan, Linlin; Long, Zhimin; Nie, Shaoping
Abstract : Scope: Type 2 diabetes is a complex metabolic and endocrine disorder worldwide, which causes severe health and economic problems. The aim of this study is to investigate the molecular mechanisms by which arabinoxylan from Plantago asiatica L. attenuates type 2 diabetes from the perspective of urine metabolomics. Methods and Results: High‐fat diet and streptozotocin‐induced type 2 diabetic rats are treated with arabinoxylan, then the urine samples are collected for untargeted metabolomics analysis by UPLC–Triple‐TOF/MS. Diabetes causes significant increases in the levels of acetone, glucose, 2‐oxoglutarate, and leucine, and significant decreases in the concentrations of creatine, histidine, lysine, l ‐tryptophan, hippurate, l ‐cysteine, kynurenine, and arabitol as compared with normal rats ( p  < 0.01). And these 12 metabolites (with VIP cut‐off value > 1) can be used as biomarkers in type 2 diabetes. A total of 21 urinary metabolites are significantly improved by arabinoxylan administration in diabetic rats, and these metabolites are mainly involved in TCA cycle, and metabolism of lipid and ketone body, taurine and hypotaurine, tryptophan, and branched chain amino acids. Conclusion: Arabinoxylan administration improves carbohydrate, lipid, and amino acid metabolism in type 2 diabetic rats, which provide important insights into the mechanisms underlying type 2 diabetes as well as the effects of arabinoxylan. Abstract : Type 2 diabetes is a complex metabolic disorder characterized by hyperglycemia as a result of insulin resistance and relative insulin deficiency. Metabolic disorder (such as lipids, amino acids, nucleic acids, and organic acids) is found in the onset and progression of T2D. Arabinoxylan from Plantago asiatica L. attenuates type 2 diabetes by improvement of carbohydrate, lipid, and amino acid metabolism. These results indicate the potential health effects of arabinoxylan.